Contribution of Heat Generation During Charging on Thermal Behaviour of Lithium-Ion Battery for HEVs Application - Sarah Mohd Puzi, Siti; Hilmi Che Daud, Zul; Asus, Zainab; Anuar Abu Bakar, Saiful; Abu Husain, Nurulakmar; Kameil Abdul Hamid, Mohd (International Journal of Engineering and Technology, 2018)
Lithium ion battery is a suitable choice in hybrid electric vehicles (HEVs) mainly because of its high energy density. Operating temperature is an important factor influencing the performance and safety of the batteries in HEVs. For this reason, the study on the battery thermal behavior during charging and discharging is necessary. The focus of this study is to develop a battery model using Matlab/Simulink software to predict the battery thermal behavior at different charge and discharge rates. A vehicle model incorporating aerodynamic drag force, rolling resistance, hill climbing force and acceleration force is used. The battery model and the vehicle model are combined to form a series hybrid electric vehicle model able to predict the battery performance in enduring the NEDC driving cycle. Result from this study is important for better understanding of the battery thermal behaviour, so a suitable battery management system can be developed ensuring an optimum use of lithium ion batteries in automotive applications.Â  Â